The Macerata Shooting: Digital Movements of Opinion in the Hybrid Media System - Anselmi, Guido; Maneri, Marcello; Quassoli, Fabio (Partecipazione e conflitto, 2022)
The role of Twitter in the organisation of political action – either by supporting existing street-level protests or native digital mobilizations – has attracted a great deal of attention. However, the wider media, political, and cultural context in which mobilizations take place is often overlooked. In this article, we analyse the trajectory of a digital movement of opinion that reacted to the shooting of black people by a right-wing militant in the Italian town of Macerata in 2018. Using a dataset of 571,996 tweets captured over 31 days, and employing a mix of machine learning, network analysis and qualitative investigation, we study how factors both external and internal to the platform sealed the fate of that movement. We maintain that the permeability of Twitter to outer divided arenas and its re-intermediation by political leaders are key to the transformation of protest movements into polarised crowds.